2002
DOI: 10.1023/a:1016064511533
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A global survey of microbial genomes reveals a correlation between genome size, repeat content and lifestyle. Free-living bacteria have large genomes with a high content of repeated sequences and self-propagating DNA, such as transposons and bacteriophages. In contrast, obligate intracellular bacteria have small genomes with a low content of repeated sequences and no or few genetic parasites. In extreme cases, such as in the 650 kb-genomes of aphid endosymbionts of the genus Buchnera all repeated sequences abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…A number of common particularities characterizes genomes of obligate intracellular pathogens and symbionts as well as some extracellular symbionts that are physically isolated from the rest of the bacterial community (157,459,509,(523)(524)(525)(526)(527)(528)(529)(530)(531)(532)(533)(534)(535)(536)(537)(538)(539)(540)(541)(542). These genomes are much smaller than the genomes of free-living bacteria (from 4 to almost 30 times smaller than the E. coli genome), have a strong AϩT bias, and have very few mobile elements, regulatory systems, and pseudogenes.…”
Section: Horizontal Gene Transfer In Prokaryotesmentioning
confidence: 99%
“…A number of common particularities characterizes genomes of obligate intracellular pathogens and symbionts as well as some extracellular symbionts that are physically isolated from the rest of the bacterial community (157,459,509,(523)(524)(525)(526)(527)(528)(529)(530)(531)(532)(533)(534)(535)(536)(537)(538)(539)(540)(541)(542). These genomes are much smaller than the genomes of free-living bacteria (from 4 to almost 30 times smaller than the E. coli genome), have a strong AϩT bias, and have very few mobile elements, regulatory systems, and pseudogenes.…”
Section: Horizontal Gene Transfer In Prokaryotesmentioning
confidence: 99%
“…In previous studies, large bacterial genomes were characterized as free-living with few pseudogenes and slow generation time [3], [41]. We found that the microbes in Sed12 and Sed222 had large genomes that included many incomplete gene copies.…”
Section: Discussionmentioning
confidence: 78%
“…However, this process may have been slow because nutrients derived from organic debris would be expected to be largely consumed by the microbes and hydrothermal reactions in the surface layer [43] and were probably scarce in the deep layers of the sediment. This may result in slow growth of the microbes, uptake and transformation of external DNA and then a slow generation time like that described for soil microbes [3], [41]. A determining step for genome deterioration is genome replication, during which defective genes and redundant fragments are removed by homologous recombination mediated by repeats and transposases [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conserved hypothetical proteins of unknown function were also abundant among the largest nonOIE proteins and absent in OIE proteomes. The absence of large proteins in OIE proteomes can be explained by the loss of lifestyle-specific proteins, present as individual loci or as genomic islands (i.e., Frank et al 2002), due to relaxed selection for these functions under the constant, intracellular host conditions. Alternatively, there might have been strong selection for the loss of these large accessory proteins early in genome reduction (Lee and Marx 2012), although the cost of having these large proteins for OIEs is not clear.…”
Section: Discussionmentioning
confidence: 99%